Baseline characteristics of outpatients with heart failure according to phenotype: preliminary analysis from SMYRNA-HF registry - Şentürk, Bihter; Çelik, Ahmet; Bekar, Lütfü; Uyan, Umut; Tülüce, Selcen yakar; Güneş, Hakan; Kerkütlüoğlu, Murat; Çoner, Ali; Kılıçaslan, Barış; Çetin, Nurullah; Çolak, Ayşe; Açar, Burak; et al. (The European Research Journal, 2022)
Objectives: SMYRNA-HF study is a prospective multicenter registry study to determine the profiles of patients with heart failure (HF) in Turkey. This study aimed to present the baseline characteristics of preliminary cohort by comparing them according to different HF phenotypes. Methods: The first SMYRNA-HF cohort included outpatients with HF from 9 centers. Patients were classified into three HF phenotypes as HF with reduced ejection fraction (HFrEF), mildly reduced EF (HFmrEF), and preserved EF (HFpEF) as recommended by guidelines. Results: Overall, 298 patients were included in this preliminary analysis that 57% of the patients were classified as having HFrEF, 33.3% as having HFpEF, and 9.7% as having HFmrEF. Female gender was more common in HFpEF (p = 0.003). Age, frequency of diabetes mellitus, use of angiotensin-converting enzyme inhibitors/angiotensin receptor blocker, use of beta-blocker, use of daily loop diuretic, heart rate, blood urea nitrogen levels, lipid profiles, hemoglobin, white blood cell, platelet levels were similar among three HF phenotypes. Body mass index (BMI) (p < 0.001), frequency of hypertension (HT) (p < 0.001), and atrial fibrillation (AF) (p = 0.015) were higher in HFpEF. Ischemic etiology (p < 0.001) was less frequent in HFpEF. Use of mineralocorticoid receptor antagonist was higher in HFrEF (p < 0.001). Conclusions: Our study presented the baseline characteristics of outpatients with HF in Turkey. There were significant differences among HF phenotypes in terms of gender, BMI, frequency of HT, AF, and ischemic etiology. Treatment implementations seem to follow the guidelines. Although the rates are low, new treatment approaches recommended in the most recent guidelines seem to enter clinical practice.